MENANAMKAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DI FAKULTAS HUKUM - Suwardi, Suwardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze the implementation of Islamic Religious Education values in the Faculty of Law to shape law graduates with integrity and a strong sense of justice. The research employs a qualitative descriptive-analytical method through interviews, observations, and document analysis. The findings indicate that Islamic values have been introduced through curricular and extracurricular activities; however, their integration into legal education has not been fully optimized. Islamic Religious Education plays a strategic role in developing students’ character, ethics, and legal culture. Therefore, strengthening the integration of religious values is essential to support a humane, ethical, and justiceoriented legal education system. Keywords: Islamic Religious Education, Law Faculty, Character Building